Goldfish Bowl Panel: Software Development Analytics - Menzies, Tim; Zimmermann, Tom (Proceedings of the 34th International Conference on Software Engineering (ICSE 2012 SEIP Track), 2012)
Gaming companies now routinely apply data mining to their user data in order to plan the next release of their software. We predict that such software development analytics will become commonplace, in the near future. For example, as large software systems migrate to the cloud, they are divided and sold as dozens of smaller apps; when shopping inside the cloud, users are free to mix and match their apps from multiple vendors (e.g. Google Docs' word processor with Zoho's slide manager); to extend, or even retain, market share cloud vendors must mine their user data in order to understand what features best attract their clients. This panel will address the open issues with analytics. Issues addressed will include the following. What is the potential for software development analytics? What are the strengths and weaknesses of the current generation of analytics tools? How best can we mature those tools?